A novel approach to correlate the salivary exosomes and their protein cargo in the progression of cognitive impairment into Alzheimer's disease - Rani K.; Rastogi S.; Vishwakarma P.; Bharti P.S.; Sharma V.; Renu K.; Modi G.P.; Vishnu V.Y.; Chatterjee P.; Dey A.B.; Nikolajeff F.; Kumar S. (My University, 2025)
Background: Cognition is the ability of a person to think, remember, and interconnect ideas from various dimensions to strive for solutions. Cognitive defects accompany all forms of dementia and the decline in cognition is a most feared aspect. Mild cognitive impairment is considered as a transitional phase and the progressive loss in cognition can finally lead to Alzheimer's disease. New Method: In this study, we demonstrated a novel method based on nanoparticle tracking analysis (NTA) technique to directly correlate salivary exosomes concentration with the progression of cognitive impairment (CI) in Alzheimer's disease (AD).This could open up the possibility for an early and cost-effective screening of Alzheimer's disease. Results: Using our novel method, the total salivary exosomes concentration was measured by NTA technique, followed by validation of key exosomal cargo proteins through an automated western blot analyzer. We observed significant differences in salivary exosomes concentration among the groups of cognitively impaired and Alzheimer's disease patients (p = 0.0023) compared to the healthy control cohort. The method was validated through CD63 (exosomes surface marker) fluorescent antibody based quantification, which yielded a similar outcome (p = 0.0286). We further corroborated our findings with the expression level of oligomeric amyloid-beta, phosphorylated-tau protein from salivary exosomes. The Aβ oligomer/fibril abundance (p = 0.0291), phospho-tau (p = 0.0325) and Aβ protein abundance (p = 0.0198) was significantly higher in Alzheimer's and cognitively impaired patients in comparison to the healthy controls. Comparison with Existing Method(s): There are few molecular biomarkers available to differentiate between various stages of cognitive impairment. Moreover, the current methodologies utilizing the few biomarkers available are either invasive or expensive; also, for a patient with mild cognitive complains, it is impractical to use these as a screening tool. Conclusion: Our initial results indicate that the salivary exosomes concentration based on the nano-tracking technique has the potential to be used as a cost-effective screening method for early disease detection. © 2020 Elsevier B.V.